PREVALENCE OF SELECTED MINOR AILMENTS OF UNDER FIVE CHILDREN AND TREATMENT SEEKING BEHAVIOR AMONG MOTHERS ATTENDING IMMUNIZATION CLINIC IN SELECTED HOSPITAL, KOLKATA - Adhya, Subarna; Das, Reshmi (International Journal of Research -GRANTHAALAYAH, 2024)
A descriptive study entitled to identify the prevalence of minor ailments and treatment seeking behavior among the mother of under five children in the selected immunization clinic of Kolkata, West Bengal. Objective of the study was to find out the occurrence of selected minor ailments of under five children and treatment seeking behavior among mother. The investigator adopted descriptive survey research approach with descriptive survey research design. She selected 100 mothers of under five children by convenient sampling technique. Data were collected with valid and reliable semi-structure interview schedule. The findings of the study revealed that Occurrence of the minor ailments within the study population was 96%, suffering were ranging from one to five problems found in the same children. The most common minor ailments of under five children are common cold & cough (87%), (43%) diarrhea, (36%) minor injury, (29%) skin rash & minor injury, conjunctivitis (18%), constipation (12%), dental caries (11%), oral thrush (9%). For these minor ailments related problems most of the mothers in case of common cold & cough, conjunctivitis, diarrhea, skin rash were seeking treatment from doctor advice as they thought they can discuss freely. In case of worm infestation, constipation and minor injury majority mothers taken sought treatment used the different home remedies. Maximum mothers for dental caries did not seek treatment as they thought no need of any treatment for their children. In this study there is significant association between treatment seeking behavior of diarrhea with age of the child and educational status of the mother. This study can be implicated in different field of nursing such as nursing education, practice, research and administration. This study may be replicated with the large randomization sample in another setting, or comparative study can be done between urban and rural areas.